1981
DOI: 10.1161/01.atv.1.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Flow studies in a model carotid bifurcation.

Abstract: Boundary layer separation in a plexiglass model carotid bifurcation was investigated in relation to the origin of atherosclerotic plaque clinically found in this region. Our model was comparable to a human carotid in both dimensions and geometry. T he predilection for atherosclerosis to occur at bifurcations in the arterial tree is well documented. 1 ' 2 This finding led to the hypothesis that hemodynamic factors are in some way involved in atherogenesis, although the precise nature of the flow or pressure cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…The separated flow zone does not appear to exist during the brief period of early systole in the model, for forward flow is observed throughout the sinus during this time. As the flow waveform reaches the decreasing velocity phase, however, separation occurs rapidly and its location migrates along the outer wall, becoming stable during diastole, hi a similar study, LoGerfo et al (1981), reported little qualitative difference in carotid bifurcation flow fields between steady and pulsatile flow. In a study of flow and plaque localization in a cast of a human aortic bifurcation, Friedman et al (1981), found a negative correlation between intimal thickness and wall shear rate.…”
Section: Discussionmentioning
confidence: 85%
“…The separated flow zone does not appear to exist during the brief period of early systole in the model, for forward flow is observed throughout the sinus during this time. As the flow waveform reaches the decreasing velocity phase, however, separation occurs rapidly and its location migrates along the outer wall, becoming stable during diastole, hi a similar study, LoGerfo et al (1981), reported little qualitative difference in carotid bifurcation flow fields between steady and pulsatile flow. In a study of flow and plaque localization in a cast of a human aortic bifurcation, Friedman et al (1981), found a negative correlation between intimal thickness and wall shear rate.…”
Section: Discussionmentioning
confidence: 85%
“…This predilection corresponds to the observed regions of low wall shear stress, flow separation, flow reversal, and helical flow in this location in models of the carotid bifurcation. [24][25][26] Indeed, in 78% of the severely atherosclerotic bifurcations in this study, the bulk of the plaque in the ICA arose from the NFDW. In these cases, the maximal stenosis was usually within 10 mm of the flow divider.…”
Section: Discussionmentioning
confidence: 72%
“…Flow separation throughout the entire cycle in their study occurred at flow ratios of 0.15 and 0.30 in models that simulate the aortic bifurcation. 18 LoGerfo et al, 19 using a model of the carotid bifurcation indicated that flow separation during steady flow occurred at a flow ratio of 0.28. Similar observations during pulsatile flow were also made by Ku and Giddens 20 using a model of the carotid bifurcation.…”
Section: Discussionmentioning
confidence: 99%